The importance of biological asset disclosures to the relevant user groups. Issue 2 (3rd April 2019) - van Biljon, Marilene; Scott, Deon
ABSTRACT: Financial statements are prepared and presented to reflect an organisation's financial position and financial performance and to provide useful information for decision-making (IASB, 2018a). The underlying accounting policies and related notes on biological assets must be presented in such a way that users can understand the transactions and valuation considerations that affect their performance (IASB, 2018a). Financial statement valuations and disclosures are informed by the requirements of the prescribed International Accounting Standards, which presumes that users "have a reasonable knowledge of business and economic activities and accounting and have a willingness to study the information with reasonable diligence" (IASB, 2018a). The accounting standards thus urges reporters to consider the usefulness of the information disclosed in the financial statements, as it may influence the decisions of users (IASB, 2018a). In systematically documenting the decision-enhancing disclosure for biological assets as required by users, the reporters have a comprehensive guideline to ensure that the disclosure is objective and a more accurate presentation of the real value. A consideration of the expectations of reporters may also address the general biological asset valuation challenges experienced in the industry. The detailed disclosures might attract investments, enhance market comparability and assist the users of the related financial information to understand the performance of biological assets.